Insights into the status and distribution of pangolins in Togo (West Africa) - Segniagbeto, G.H.; Assou, D.; Agbessi, E.K.G.; Atsri, H.K.; D'Cruze, N.; Auliya, M.; Fa, J.E.; Luiselli, L. (Wiley, 2021)
Pangolins are considered among the most threatened mammal species, both globally and also in Africa. However, almost nothing is known on their status and distribution across wide areas of their range, particularly in West African countries. Here, we assess the status and distribution of pangolin species in Togo. Fieldwork was carried out in five localities around the Fazao Malfakassa National Park, five sites around the Togodo Protected Areas Complex (Togodo North and Togodo South National Parks), ‘Les Deux Béna’ and Missahohe Forest Reserves, Yikpa‐Dzigbe, Evou and Afagnan Community Forests. In all of these protected areas and forest islands, only one pangolin species was recorded: the white‐bellied pangolin (Phataginus tricuspis); we found no evidence of the giant ground pangolin (Smutsia gigantea), a species that now appears unlikely for Togo. Due to their nocturnal behaviour, we searched for pangolins by spotlighting and estimated their relative abundance using the Kilometric Index of Abundance. Our results show that P. tricuspis is still relatively abundant in suitable habitats in Fazao‐Malfakassa National Park, in Togodo North National Park and in the Assoukoko Forest Reserve. These habitats are dense remnant forest patches where numerous termite mounds and ant nests occur. The present study provides unprecedented information on the status of pangolins in Togo to help inform the development of a conservation programme for this species in this country.